Calpain cleaved-55kDa N-terminal huntingtin delocalizes from neurons to astrocytes after ischemic injury - Kim, S. C.; Chung, J-Y.; Im, W.; Kim, M.; Kim, M. (Cellular and Molecular Biology, 2011)
The huntingtin (htt) mutation causes a polyglutamine expansion in the N-terminal region of protein. Mutant N-htt proteolytic fragments aggregate and cause cell death in Huntington's disease (HD). The normal huntingtin also can be cleaved by calpain and produce N-terminal htt fragments following ischemic injury, but the fate of cleaved fragment in dead neurons in the brain are unclear. To determine the localization of huntingtin following proteolysis, we examined htt expression after transient ischemic injury. Huntingtin immunoreactivity in mixed cultures of neuronal and astrocytes-derived clonal cells showed alteration of immunoreactivity from neurons into astrocytes. In the brain, both focal and global ischemia induced reactive astrocytes that were co-immunoreactive for huntingtin with elevated GFAP expression. The immunoreactive huntingtin was 55kDa calpain-cleaved N-terminal fragment, which appeared initially in the process, and extended into the cytoplasm of astrocytes. The results showed, after ischemic injury, huntingtin accumulated in astrocytes indicating that astrocytes may play a role in uptake of cleaved N-htt fragments.